Theism and Public Policy
XV, 180 p.
Keywords: Does theism dominant the language and practices of public life in the United States? This volume explores this question from a humanist perspective, and in so doing it provides insight into the relationship of religion to public policy, and offers ways to advance a more democratic and secular public arena.